Geochemical Tools Identify the Origins of Chinook Salmon Returning to a Restored Creek. Issue 1 (11th January 2021) - Willmes, Malte; Jacinto, Emily E.; Lewis, Levi S.; Fichman, Rachel A.; Bess, Zachary; Singer, Gabriel; Steel, Anna; Moyle, Peter; Rypel, Andrew L.; Fangue, Nann; Glessner, Justin J.G.; Hobbs, James A.; et al.
Abstract : Populations of Chinook Salmon Oncorhynchus tshawytscha in California are in decline due to the combined effects of habitat degradation, water diversions, and climate change. Reduced life history diversity within these populations inhibits their ability to respond to these stressors. Putah Creek, a small creek in California's Central Valley that once supported Chinook Salmon, is undergoing restoration to provide spawning habitats for this imperiled species. Beginning in 2014, increasing numbers of Chinook Salmon spawned throughout the creek, and emigrating juveniles were observed in the following months. Here we used otolith annual growth bands and microchemistry to investigate the age structure and natal origins of the adult spawners. Most individuals were 2 or 3 years old, and they originated from at least seven different natal sources, overwhelmingly from Central Valley hatcheries (~88%). These findings highlight that straying fall‐run Central Valley Chinook Salmon can rapidly utilize restored habitats, potentially establishing new populations. However, to facilitate local adaptations, straying rates and gene flow will have to be managed over time. Reconnecting migratory pathways and restoring many small and diverse streams, like Putah Creek, provides an opportunity to increase life history diversity, strengthening the recovery and resilience of Chinook Salmon.